2011
DOI: 10.1523/jneurosci.6582-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

CLIP-170 and IQGAP1 Cooperatively Regulate Dendrite Morphology

Abstract: Dendritic arbors are compartments of neurons dedicated to receiving synaptic inputs. Their shape is an outcome of both the intrinsic genetic program and environmental signals. The microtubules and actin cytoskeleton are both crucial for proper dendritic morphology, but how they interact is unclear. The present study demonstrates that microtubule plus-end tracking protein CLIP-170 and actin-binding protein IQGAP1 regulate dendrite morphology of rat neurons by coordinating the interaction between microtubules an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
118
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(126 citation statements)
references
References 61 publications
7
118
0
1
Order By: Relevance
“…The animals used to obtain neurons for tissue cultures were sacrificed according to a protocol approved by the First Ethical Committee, Warsaw, Poland. Primary rat hippocampal and cortical cultures were prepared from embryonic day 18 (E18) rat brains according to Banker and Goslin (31) with modifications and transfected with Lipofectamine2000 (Invitrogen) as recently described (8,30). For insulin-induced growth, immediately after transfection, the cells were transferred to a regular culture medium that contained a reduced concentration of B27 (0.2% instead of 2%; Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The animals used to obtain neurons for tissue cultures were sacrificed according to a protocol approved by the First Ethical Committee, Warsaw, Poland. Primary rat hippocampal and cortical cultures were prepared from embryonic day 18 (E18) rat brains according to Banker and Goslin (31) with modifications and transfected with Lipofectamine2000 (Invitrogen) as recently described (8,30). For insulin-induced growth, immediately after transfection, the cells were transferred to a regular culture medium that contained a reduced concentration of B27 (0.2% instead of 2%; Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, RhoA, Rac1, and cdc42 are among the best-characterized regulators of dendritic growth (22)(23)(24). We previously showed that active Akt enhances dendritic arborization (5,8). Nevertheless, the involvement of mTORC2 in the development of mammalian neurons has not been directly demonstrated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…28 In rat neurons, CLIP1 together with IQGAP1 controls dendrite morphology, again possibly by regulating the interaction between MTs and the actin cytoskeleton. 9 The second zinc knuckle in the C-terminal domain of CLIP1 takes part in direct interaction with the dynactin subunit 1, DCTN1 (P150 Glued ) of the dynein/dynactin complex. 29 Dynactin (dynein activator) is essential for every cellular function of cytoplasmic dynein.…”
Section: Discussionmentioning
confidence: 99%
“…MAP2 knockout mice show altered MT spacing and reduced dendrite arbor size (Harada et al 2002;Teng et al 2001). Other MT-related proteins, such as the plusend binding proteins CLIP-170 and CLASP2, and the minus-end binding protein CAMSAP2, are also involved in dendrite development (Beffert et al 2012;Swiech et al 2011;Yau et al 2014). Moreover, the MT-destabilizing proteins stathmin and SCLIP, or MT-severing proteins, like spastin and katanin p60-like 1, have been reported to regulate dendrite development (Jinushi-Nakao et al 2007;Lee et al 2009;Ohkawa et al 2007;Poulain et al 2008;Stewart et al 2012;Ye et al 2011).…”
Section: Functions Of Axon and Dendritic Microtubulesmentioning
confidence: 99%